The hidden cost of winning a medal: a narrative review on the mental health of elite athletes - Smaranda, A.-M.; Vlaic, A.; Caramoci, A.; Ionescu, A.-M. (British Journal of Sports Medicine, 2021)
Background Athletes have started a public conversation about the psychological struggles they are facing. To create a safer psychological environment, the sporting community has the duty to support this movement by increasing awareness, providing educational resources, addressing stigma and encouraging mental health research.